Konsep Pendidikan Islam di Era Globalisasi: Studi Pemikiran KH. Abdurrahman Wahid - Hidayat, Arif (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This research aims to explore the concept of Islamic education in the era of globalization from the perspective of KH. Abdurrahman Wahid. The study is based on concerns about the impact of globalization, referred to as "future shock" by the renowned futurologist Alvin Toffler. The researcher observes that the education sector in Indonesia lacks a clear concept to face this wave of globalization. Therefore, this study seeks to delve into the concept of Islamic education in the era of globalization, characterized by neo-modernism, which involves preserving traditional values while incorporating Western modernization. The research adopts the Library Research method, focusing on various literature sources such as books, articles, and newspapers. Data collection employs documentary techniques. The study utilizes a historical-philosophical approach and content analysis as the analytical method. The findings reveal that the concept of Islamic education in the perspective of KH. Abdurrahman Wahid during the era of globalization consists of three core discussions. Firstly, the goals of Islamic education encompass neomodernism, liberation-based education, and multiculturalism-based education. Secondly, the Islamic education curriculum includes the formation of Islamic personality, Islamic culture development, and the advancement of life sciences, skills, and expertise. Thirdly, the methods of Islamic education involve political, cultural, and socio-cultural strategies. Additionally, the concept of Islamic education from the perspective of KH. Abdurrahman Wahid exhibits an eclectic ideology, indicating its distinctive characteristics in the realm of educational ideology. This research hopes that the concept can serve as an alternative reference for the education sector in Indonesia to confront the challenges of globalization.